Constrained remote control of construction machine with time-varying delay and packet loss. (17th January 2023) - Ishikawa, Takahiro; Masuda, Michiya; Uda, Shunsuke; Yokoyama, Koichiro; Hamamoto, Kenniti; Kogiso, Kiminao
Abstract : This study developed a constrained remote control system for a crawler dump (C50-R, YANMAR Co.), which was experimentally validated in the testing field of Kajima Corporation. The remote-controlled crawler dump fulfilled the input constraints and tracked to a reference position and rotation angle in the presence of time-varying transmission delays and consecutive packet losses. The developed autonomous and remote control technology is expected to contribute to the compensation for the labor shortage in the construction industry and improve the workplace environment. GRAPHICAL ABSTRACT: UF0001